PENGARUH MODEL SNOWBALL THROWING TERHADAP HASIL BELAJAR IPS KELAS V SDN 26 PONTIANAK TENGGARA - Ronal, Ronal; Marli, Suhardi; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze how much influence the application of snowball throwing model the learning outcomes of students in Social Studies of class V Elementary School 26 Pontianak Southeast. This study used an experimental method, and the form of this reserach is Pre-Experimental Design with the research design of one group pretest-posttest design. The samples in this study were all students of class VA Elementary School 26 Pontianak Southeast consisting of 30 students. Data collection tool that is used in the form of tests of student learning outcomes in the form of multiple choice questions numbered 50. Based on the statistical calculation of the average results obtained studying the experimental class pre-test is 59.47, while the average of the experimental class post-test is 81,07. From the calculation of effect size (ES) obtained 1,85 (high criterion). It can be concluded that there are significant snowball throwing model influence on student learning outcomes.Â Â Keywords: Cooperative Learning, Learning Outcomes, Snowball Throwing Model